Eco-friendly enhancement of optical and structural properties in polyvinyl alcohol films via eggplant peel dye doping - Othman K. Hamaamin; Hewa O. Ghareeb; Sewara J. Mohammed (Scientific Reports)
Abstract This study presents an eco-friendly strategy to enhance the optical and structural properties of polyvinyl alcohol (PVA) films through doping with eggplant peel dye (EPPD), a natural pigment extracted from agricultural waste via a green aqueous synthesis (~ 33% yield from 30 g of peel). EPPD was uniformly dispersed in PVA films (PVA-D1, PVA-D2, PVA-D3) using an ultrasonic-assisted solution casting technique, with chitosan (CS) added to prevent fungal growth. Comprehensive characterization (Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), ultraviolet-visible spectroscopy (UV-Vis), and differential scanning calorimetry (DSC)) confirmed successful integration of EPPD, revealing its polyhydric alcohol content, amorphous nature, and uniform distribution within the polymer matrix. Doping with EPPD significantly reduced the optical band gap from 6.314 eV (pure PVA) to 1.8 eV (PVA-D3), introducing localized states that enhanced light absorption (peaking at 554 nm in PVA-D3), as supported by Tauc’s model (transition type: direct allowed → direct forbidden) and dielectric loss analysis. Additionally, the refractive index increased from 1.165 to 1.27, while the optical dielectric constant (ε₁) improved from 1.366 to 1.609 due to enhanced charge carrier density. XRD analysis revealed a decrease in crystallinity from 30.50% (pure PVA) to 18.11% (PVA-D3), leading to a reduction in the glass transition temperature (from 30.5 °C to 25 °C) and melting temperature (from 240 °C to 194 °C). The Urbach energy (Eu), an indicator of structural disorder, increased from 0.43 eV (pure PVA) to 0.62 eV (PVA-D3), reflecting a higher density of localized states in the amorphous matrix and broader tail states in the band structure. These tunable optoelectronic properties position EPPD-doped PVA films as promising candidates for various applications, including UV-protective textiles, smart packaging, biomedical dressings, and energy-efficient optoelectronic devices.